What's next for size-sound symbolism? - Ekström, Axel G. (Frontiers in Language Sciences, 2022)
This text reviews recent research in spoken-language size-sound symbolism, the non-arbitrary cognitive mapping of size properties to speech acoustic properties. Evidence from a wide range of research works, and explanations of the observed phenomenon, are surveyed. Recent findings from research on the relationships between fundamental frequency, vowel articulation, consonant articulation, phonation type, mora count, and phonemic position, are briefly discussed. It is also argued that a satisfactory explanatory model of phonetic size-sound symbolism should meet two criteria: they should be able to explain both (1) the relationship between size and speech acoustics, and (2) the inconsistent findings of symbolism observed across languages in the relevant literature. Five theories are briefly discussed: The frequency code, Embodied cognition, Sound-meaning bootstrapping, Sapir-Whorf hypotheses, and Stochastic drift. It is contended that no currently available explanatory model of size-symbolism adequately meets both criteria, but that a combination of perspectives provides much of the necessary depth. Future directions are also discussed.